The effect of nutritional status on mesiodistal and bucco/ lingual or palatal diameters of permanent teeth among fifteen years old students - Zaid S Ahmed; Ban S Diab (College of Dentistry/ University of Baghdad, 2016)
Background: Malnutrition during human growth affects the size of the tissues at different stages of life, body proportions, body chemistry, as well as quality and texture of tissues. Teeth are particularly sensitive to malnutrition. Malnutrition may affect odontometric measurement involving tooth size dimensions. The aim of this study was to estimate the effect of nutrition on teeth size dimension measurements among students aged 15 years old. Materials and methods: This study was conducted among malnourished group in comparison to well-nourished group matching with age and gender. The present study included 167 students aged 15 years (83 malnourished and 84 well-nourished). The assessment of nutritional status was done by using body mass index (BMI). Odontometric measurements included three different orientations. For both upper and lower study models, photographs were taken using special photographic apparatus for each student, and the data were then analyzed using special computer software. For permanent dentitions, two linear measurements (mesiodistal and bucco \lingual or palatal) were utilized, representing tooth diameters for each tooth. Results: Among students aged 15 years, the findings revealed that all means of mesiodistal and bucco-lingual diameters values of maxillary and mandibular teeth were lower among malnourished than well-nourished groups with statistically significant, except for mesiodistal diameters of both second molar, second and first premolar of maxillary teeth, second premolar, first premolar and lateral incisor of mandibular teeth and for bucco-palatal diameters of second and first premolar of maxillary teeth, second molar and lateral incisor of mandibular teeth. Conclusion: Malnutrition effect on minimize the odontometric measurements (mesiodistal and bucco-lingual diameters) among students aged 15 years.